Wake Up and Smell the Media: Developing a Culture Model of the Olfactory Epithelium - Peterson, Jesse. (2017)
Abstract: The olfactory neuroepithelium (OE) is capable of regeneration throughout adult life to an extent unparalleled within the mammalian nervous system. The OE accomplishes this regeneration through the concerted effort of at least two resident stem cell populations: the flattened, horizontal basal cells (HBCs) and the globose basal cells (GBCs) that reside just apical to the HBCs and below the olfactory sensory neurons (OSNs). HBCs exhibit the behavior of a classic reserve stem cell: they are quiescent and slowly dividing until activated by severe tissue loss. In contrast, GBCs are highly proliferative and reactive, responding to daily cell turnover by frequent differentiation. Recently, the transcription factor p63 was identified as the master regulator of HBC quiescence, providing a unique opportunity to investigate HBC activation and to further explore stem cell heterogeneity. In this thesis I develop a set of additional tools to study p63 in vitro and explore the relationship between p63 and the major developmental pathway Wnt. In Chapter 3 I demonstrate an OE basal cell primary culture that may be utilized to further investigate p63 regulation. I establish a relatively pure basal epithelial culture based on the classic bronchial epithelial growth media with modifications to accommodate the metabolic demands of neurobasal stem cells. The histological profile of these cells is compared with the basal progenitors and mature cell types of the OE and found to be identical to p63+ HBCs in vivo. I confirm that these cells remain undifferentiated in culture until treated with either retinoic acid or by genetic ablation of p63 which results in differentiation into neuronal and non-neuronal cell types. By utilizing genetic lineage traces, I can identify the cells of origin for these HBC-like cells and determine they come from Ascl1+ GBCs as well as HBCs. Interestingly, immediate neural precursor Neurog1+ GBCs can only give rise to basal cultures following olfactotoxic lesion. The plasticity of olfactory cultures is further demonstrated by directing them toward a respiratory cell fate. Finally I develop a 3D air-liquid interface based system for generating complex neuronal and non-neuronal organoids. Chapter 4 is broad characterization of Wnt signaling in HBCs under normal physiological conditions and during recovery from injury. I also explore the consequences of aberrant Wnt expression in HBCs. Utilizing a Wnt reporter model I identify its peak activity in the basal compartment after olfactotoxic lesion and through immunohistochemistry, quantitative PCR, and transgenic animal models I begin to characterize the previously unexplored relationship between Wnt, p63 and HBC proliferation. My data suggest that Wnt may be dispensible for HBC self-renewal, and utilizing mutant models I find that HBCs appear relatively resistant to moderate Wnt manipulation in contrast to recent findings in GBCs. However, in the presence of a stabilized β-catenin, HBCs exhibit dysplastic growth. I identify the non-canonical Wnt receptor Ror2 in HBCs, which to our knowledge represents the first histological marker that distinguishes between these cells and the basal cells of the neighboring respiratory epithelium. I proceed to explore Ror2 expression changes relative to canonical Wnt levels after injury, although the significance of this relationship remains to be determined. Taken together, this thesis introduces a number of new tools for investigating the role of p63 in HBC quiescence/activation and clarifies our understanding of the relationship between Wnt and p63.; Thesis (Ph.D.)--Tufts University, 2017.; Submitted to the Dept. of Cell, Molecular & Developmental Biology.; Advisor: Grace Gill.; Committee: Amy Yee, Li Zeng, and Bradley Goldstein.; Keyword: Cellular biology.